Distribución de cámaras de videovigilancia en almacenes de productos de exportación usando el algoritmo Spider Monkey Optimization (SMO) - (:unkn) unknown (Universidad de La Rioja, 2024)
As part of the industrial security tasks, the correct control of the activities of a product warehouse must be supported by means of closed-circuit camera surveillance systems (CCTV) on a permanent basis. The location of these devices must be sufficientl...
Keywords: Videovigilancia; Optimización